Health status and mental health among elderly in rural, Thailand: a community based cross-sectional study - Prasansri, Alongkot; Hachawi, Chidchai; Chaiwcharn, Tamaporn (International Journal Of Community Medicine And Public Health, 2024)
Background: The transition to an aging society in Thailand over the past several years has had significant impacts across various sectors, include the quality of life for the elderly, health and mental health problems, and the need to expand healthcare services. Therefore, it is essential to investigate the health and mental health status of the elderly in Thai society. Methods: A community based cross-sectional study was conducted to assess health status and mental health among elderly rural areas. A total of 158 samples were collected from the district of U Thong, Suphan Buri province during August and September 2023. Data were collected using the Basic Geriatric Screening (BGS), and Thai Mental Health Indicators version 2007 (TMHI-15) questionnaires. The demographic characteristics questionnaire was also applied. Descriptive statistics were utilized for data analysis. Results: Out of a total of 158 samples, 65.2% were female. The mean age of the participants was 72.2±8.5 years. The prevalence of chronic diseases among the participants was 69.0%. Nutritional status assessment revealed that 57.0% of the participants were overweight or obese based on BMI. Disability data indicated that 10.1% of the participants had hearing impairments, 63.9% had visual impairments, and 71.5% had oral health problems. Overall, 8.2% of the elderly had limitations in activities of daily living, and 19.6% experienced poor mental health. Conclusions: The result showed that important health problems in elderly were non-communicable diseases, disability, and mental health.